2011
DOI: 10.9744/jak.13.1.47-56
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Resiko, Kualitas Manajemen, Ukuran dan Likuiditas Bank terhadap Capital Adequacy Ratio Bank-Bank yang Terdaftar di Bursa Efek Indonesia

Abstract: Tujuan penelitian ini adalah untuk mengetahui apakah efek risiko, kualitas manajemen, ukuran bank dan likuiditas mempunyai pengaruh terhadap Capital Adequacy Ratio (CAR). Penelitian ini adalah penelitian eksplorasi. Pengambilan sampel menggunakan purposive sampling terhadap bank umum go public yang terdaftar di Bursa Efek Indonesia dan memiliki laporan keuangan yang lengkap selama periode [2003][2004][2005][2006][2007][2008] The result of research indicated that index risk (risk of asset turnover), management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
1
3
1
8
Order By: Relevance
“…These findings reinforce study published by Permatasari & Novitasary (2014), which concluded that the bank's high capital adequacy ratio is a result of suboptimal capital management that is unaffected by Good Corporate Governance standards. These findings contrast with those of Rehman et al (2010), Chitan (2012), andPrasojo (2015), all of whom assert that good corporate governance has a favorable and significant effect on the capital adequacy ratio.…”
Section: Good Corporate Governance Has a Beneficial Effect On The Capital Adequacy Ratiocontrasting
confidence: 71%
“…These findings reinforce study published by Permatasari & Novitasary (2014), which concluded that the bank's high capital adequacy ratio is a result of suboptimal capital management that is unaffected by Good Corporate Governance standards. These findings contrast with those of Rehman et al (2010), Chitan (2012), andPrasojo (2015), all of whom assert that good corporate governance has a favorable and significant effect on the capital adequacy ratio.…”
Section: Good Corporate Governance Has a Beneficial Effect On The Capital Adequacy Ratiocontrasting
confidence: 71%
“…Pembiayaan kepada nasabah, besarnya di imbangi dengan besarnya dana deposan yang wajib di kembalikan oleh bank, sehingga dana deposan yang digunakan bank untuk pembiayaan dapat di ukur oleh bank. (12).…”
Section: Rerangka Pemikiran Dan Hipotesisunclassified
“…Keberadaan bank yang sehat merupakan prasyarat bagi suatu perekonomian yang sehat (Margaretha & Setiyaningrum 2011). Bank berfungsi sebagai lembaga perantara keuangan (financial intermediary) yang menghubungan antara pihak-pihak yang memiliki kelebihan dana (surplus spending unit) dengan pihak-pihak yang memerlukan dana (deficit spending unit) serta lembaga yang berfungsi memperlancar aliran lalu lintas pembayaran.…”
Section: Pendahuluanunclassified